Problems and prospects of timeshare industry in Malaysia / Nor Fazarizan Mukhtar - Mukhtar, Nor Fazarizan (Faculty of Business and Management, 2006)
Timeshare industry has been growing among the development country. In Malaysia, it was first introduced in 1980's during recession. Previously, there are ten timeshare operators have involved in the industry, but two companies were bankrupt. Therefore, only eight companies were left actively operates in the industry. However, it is quite tough for the companies to survive in the timeshare industry. They have to face problems from the macro environment factors and handle the situation strongly to reach their future prospects. For that reason, this paper develops to identify the problems and prospects of timeshare industry in Malaysia. The framework integrates three categories of factors influencing on the problems and prospects of the industry: Products or services, price, and promotion. The model was tested with survey sample. The findings of the study indicate that the problems are actually come from the marketing mix factors.